EM radiation from electrostatic nonlinear pull‐in instability of MEMS. Issue 2 (1st January 2018) - Luo, Yong; Xu, Jiayou; Yang, Guangli; Toshiyoshi, Hiroshi
Abstract : Electrodynamics theory tells that EM waves are generated from accelerated charged particles. Conventional radiators such as antennas are understood to emit waves because of the current's distribution and accumulation in the capacitor, where electrons are accelerated. In MEMS mechanisms, charges can be accelerated by the mechanical motion, which suggests that an MEMS structure can also be a radiator. The electrodynamics to theoretically analyse the EM wave radiation from MEMS is used. During the electrostatic nonlinear pull‐in instability MEMS, where the electrostatic gap has become narrower than the 2/3 of the initial gap, the distributed charges are accelerated at a very high rate so as to generate significant power radiation in the form of EM waves. The MEMS's mechanical accelerations are analysed to calculate the transient radiations in both spatial and frequency domains.